Chitosan nanocomposite containing rotenoids: an alternative bioinsecticidal approach for the management of Aedes aegypti - Maria A. A. Bertonceli; Vitor D. C. Cristo; Ivo J. Vieira; Francisco J. A. Lemos; Arnoldo R. Façanha; Raimundo Braz-Filho; Gustavo V. T. Batista; Luis G. M. Basso; Sérgio H. Seabra; Thalya S. R. Nogueira; Felipe F. Moreira; Arícia L. E. M. Assis; et al. (Beilstein Journal of Nanotechnology, 2025)
Climate change has intensified the proliferation of disease vectors, such as Aedes aegypti, the primary transmitter of dengue, chikungunya, and zika viruses. Although the two recently licensed dengue vaccines represent a significant advancement, vector management remains the primary strategy for preventing these urban arboviruses. In this context, the development of pesticides that offer safer alternatives for the environment and human health has become urgent. In this study, a chitosan-based nanocomposite was developed as a delivery system for rotenoids isolated from Clitoria fairchildiana seeds, leveraging their larvicidal activity against third-instar larvae of Ae. aegypti. The nanocomposite was synthesized using a controlled ionic gelation method incorporating the TPP-β-CD inclusion complex, which resulted in nanoparticles with smaller size, improved polydispersity index, and enhanced stability, evidenced by a higher zeta potential. FTIR analysis confirmed rotenoid incorporation into the nanocomposite and suggested hydrogen bonding or potential covalent interaction with chitosan functional groups. Bioassays demonstrated that the nanocomposite achieved an LC50 of 91.7 ppm, representing a 23.6% increase in larvicidal efficacy compared to the rotenoids in their natural form. The nanocomposite also induced dose-dependent morphological and physiological alterations in the larvae, including damage to the peritrophic matrix, evidenced by abnormal anal excretion, and tissue melanization and formation of melanotic pseudotumors. These responses may be associated with increased production of reactive oxygen species in the larval midgut, consistent with previous findings for the nonencapsulated rotenoids. Importantly, empty nanoparticles exhibited no adverse effects on larval survival, which is attributed to the biocompatibility and nontoxic nature of chitosan, a biodegradable polysaccharide structurally related to the insect exoskeleton and widely recognized for its environmental safety. Additionally, neither rotenoids nor the CS/TPP–β-CD–rot nanocomposite exerted cytotoxic effects, confirming their favorable safety profile. These findings highlight the potential of nanotechnology to enhance the efficacy of bioactive compounds while minimizing environmental and human health risks, offering a sustainable and innovative strategy for vector control.